2007
DOI: 10.1002/pbc.20831
|View full text |Cite
|
Sign up to set email alerts
|

Ewing sarcoma/primitive neuroectodermal tumor of the kidney in a child

Abstract: A 6‐year‐old female was admitted with abdominal pain and a mass in the right abdomen. Her lactose dehydrogenase level was 1,200 IU/L, and neuron specific enolase was 120 ng/ml. Computed tomography scan confirmed a large right renal mass with necrosis. A right radical nephrectomy was performed. The tumor was completely encapsulated. Based on small round cell histology, strong MIC‐2 (CD99) positive tumor cells, and EWS‐FLI‐1 fusion transcript, Ewing sarcoma/primitive neuroectodermal tumor of the kidney was diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Other transcripts have also been reported [24, 25, 26]. As many as 20% of ES exhibit additional more complex chromosomal arrangements [11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other transcripts have also been reported [24, 25, 26]. As many as 20% of ES exhibit additional more complex chromosomal arrangements [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Extraosseous (EO) ES is usually seen in the soft tissue of the lower extremities and the paravertebral region but has also been reported to arise in the gastrointestinal tract [10], kidney [11], uterus [12] and other infrequent sites [13, 14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…PNETs are derived from primitive neural crest cells and usually occur in bone or soft tissues of the extremities, trunk, head, and neck, and less commonly in the viscera or kidneys [5,6]. However, many cases of PNET of the kidney have been reported since the original description of this condition by Seemayer et al [3], with 14 cases reported in Japan [7][8][9][10][11][12][13]. The typical histological features of renal PNET are monotonous proliferation of immature and small round cells with at least partial formation of Homer-Wright-type or Flexner-type rosettes [1,14].…”
Section: Discussionmentioning
confidence: 98%
“…[6] EO ES is generally seen in the lower extremities and the paravertebral region. It has also been reported to arise in the gastrointestinal tract, [7] kidney, [8] uterus [9] and other infrequent sites. [10][11][12] Imaging is worthwhile for local spread, resectability and metastases.…”
Section: Discussionmentioning
confidence: 99%